2023
DOI: 10.3389/fnut.2023.1081956
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four nutritional screening tools in perioperative elderly patients: Taking orthopedic and neurosurgical patients as examples

Abstract: Background and aimsMalnutrition is widely present in elderly surgical patients and is highly correlated with prognosis after surgery. However, studies comparing the effectiveness of comprehensive nutritional screening tools in geriatric surgical patients have not yet been published. The nutritional risk among elderly orthopedic and neurosurgical patients and their associated clinical indicators and outcomes was assessed using four screening tools. The aim of this study was to explore suitable tools for screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…This finding concurs with pre-existing literature. 7 , 10 , 12 , 15 , 24 Our study discovered a greater likelihood of any complication, sepsis, nonhome discharge, readmission, unplanned reoperation, and increased LOS for both degrees of malnutrition. For complications independently associated with both moderate and severe malnutrition, severe malnutrition was generally found to have stronger associations: any complication (OR 1.84 in moderate malnutrition vs. 11.70 in severe malnutrition), sepsis (OR 3.75 vs. 26.61), nonhome discharge (OR 2.09 vs. 15.75), readmission (OR 1.66 vs. 2.69), unplanned reoperation (OR 4.23 vs. 6.32), and LOS >2 days (OR 2.37 vs. 23.66).…”
Section: Discussionmentioning
confidence: 55%
“…This finding concurs with pre-existing literature. 7 , 10 , 12 , 15 , 24 Our study discovered a greater likelihood of any complication, sepsis, nonhome discharge, readmission, unplanned reoperation, and increased LOS for both degrees of malnutrition. For complications independently associated with both moderate and severe malnutrition, severe malnutrition was generally found to have stronger associations: any complication (OR 1.84 in moderate malnutrition vs. 11.70 in severe malnutrition), sepsis (OR 3.75 vs. 26.61), nonhome discharge (OR 2.09 vs. 15.75), readmission (OR 1.66 vs. 2.69), unplanned reoperation (OR 4.23 vs. 6.32), and LOS >2 days (OR 2.37 vs. 23.66).…”
Section: Discussionmentioning
confidence: 55%
“… 5 GNRI has displayed reliability and validity comparable to established nutritional assessments; notably, poor prognosis following orthopedic surgeries was most effectively predicted by GNRI scores. 16 Furthermore, studies support the use of GNRI in cases where questionnaires such as MNA cannot be performed, even encouraging the use of both assessments to allow for more accurate results. 12…”
Section: Discussionmentioning
confidence: 95%
“…Despite all three indices being associated with adverse outcomes, the superiority of one index over others has not been established. Gong et al [ 41 ] in a cohort of 167 orthopedic patients and 103 neurosurgical patients have shown that both PNI and GNRI are predictors of adverse events and longer hospital stays, but the GNRI may have a better predictive ability. In a cohort of 113 patients undergoing pancreaticoduodenectomy, Cong et al [ 42 ] have shown that all three indices were predictors of postoperative complications but PNI had the highest diagnostic efficacy.…”
Section: Discussionmentioning
confidence: 99%